2009
DOI: 10.1507/endocrj.k08e-239
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Exposure to Diethylstilbestrol Alters Expression of DNA Methyltransferases and Methylation of Genomic DNA in the Mouse Uterus

Abstract: Abstract. Perinatal exposure to diethylstilbestrol (DES) can have numerous adverse effects on the reproductive organs later in life, such as vaginal clear-cell adenocarcinoma. Epigenetic processes including DNA methylation may be involved in the mechanisms. We subcutaneously injected DES to neonatal C57BL/6 mice. At days 5, 14, and 30, expressions of DNA methyltransferases (Dnmts) Dnmt1, Dnmt3a, and Dnmt3b, and transcription factors Sp1 and Sp3 were examined. We also performed restriction landmark genomic scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 48 publications
1
47
0
2
Order By: Relevance
“…For example the estrogen-responsive lactoferrin gene seems to be up-regulated in the mouse uterus, after neonatal exposure to DES; this abnormal expression persists later in life (Nelson et al 1994) and may be attributed to an abnormal demethylation in the lactoferrin gene promoter, which seems to occurr specifically in response to neonatal DES exposure . Moreover, this demethylation state is continuously maintained in uterine tumours of DES-exposed mice, suggesting that neonatal DES treatment may not only induce tumour formation but also gene-specific demethylation, through a common cellular process, such as alterations of the expression of DNA methyltransferases and methylation of genomic DNA Sato et al 2009). Subsequent work demonstrated that other developmental genes, up-regulated after exposure to DES, also exhibit modified methylation patterns.…”
Section: Des and Epigeneticsmentioning
confidence: 99%
“…For example the estrogen-responsive lactoferrin gene seems to be up-regulated in the mouse uterus, after neonatal exposure to DES; this abnormal expression persists later in life (Nelson et al 1994) and may be attributed to an abnormal demethylation in the lactoferrin gene promoter, which seems to occurr specifically in response to neonatal DES exposure . Moreover, this demethylation state is continuously maintained in uterine tumours of DES-exposed mice, suggesting that neonatal DES treatment may not only induce tumour formation but also gene-specific demethylation, through a common cellular process, such as alterations of the expression of DNA methyltransferases and methylation of genomic DNA Sato et al 2009). Subsequent work demonstrated that other developmental genes, up-regulated after exposure to DES, also exhibit modified methylation patterns.…”
Section: Des and Epigeneticsmentioning
confidence: 99%
“…after subcutaneous injection of DES in mice and at least five investigated genomic loci showed decreased DNA methylation in the uterus of the investigated mice (Sato et al, 2009 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 12 used similar methods and experimental setup to study the changes in DNA methyltransferase (DNMT) expression and DNA methylation in epididymis of mice and found altered but increased expression of DNMT-s. (Sato et al, 2006) In some instances the transgenerational change is simply a sensitization of the organism towards a second signal. As an example, neonatal exposure of rats to BPA resulted in an increased incidence of prostate intraepithelial neoplasia (Ho et al, 2006).…”
Section: Endocrine Disruptors and Nrsmentioning
confidence: 92%
“…Subsequently, it was also found that exon 4 of the c-fos gene was extensively hypomethylated while the promoter region and intron 1 was unaffected, thereby potentially allowing for the upregulation of c-fos expression [138]. QPCR studies performed by Sato and colleagues examining the expression of Dnmts in neonatally DES exposed C57BL/6 mice, revealed that expression of Dnmt1 and Dnmt3b was decreased at PND5 in DES-treated mice, and the pattern continued until PND14 [139]. Interestingly, it was found that human leiomyoma samples had alterations in the levels of Dnmts as well, with concomitant global hypomethylation [140].…”
Section: Des In Vivo Studiesmentioning
confidence: 99%